Labor Market Reform Options to Boost Employment in South Africa - Duval, Romain; Ji, Yi.; Shibata, Ippei (Washington, D.C. : International Monetary Fund, 2021)
Raising South Africa's low employment rate to levels seen in emerging market or advanced economy peers could raise GDP per capita by 50 to 60 percent and reduce income inequality dramatically in the long term. By putting further strain on an already fragile labor market, Covid-19 has raised the urgency of action. This paper reviews labor market policy and other reform options to enhance South Africa's job market performance, drawing from international evidence and new analysis. We find much scope for improving the design of key labor market institutions-including collective bargaining and employment protection legislation-and active labor market policies to improve job seekers' prospects. These reforms should come hand-in-hand with others, such as in the areas of education or product market regulation, that may work pay. Labor market and other reforms would primarily benefit disadvantaged groups such as youth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Labor Market Performance; Paper Reviews Labor Market Policy; Product Market Regulation; Reform Option; Youth Employment; South Africa